Evaluasi Hasil Pembelajaran Elemen User Interface Dalam Pemrograman Berbasis Teks, Grafis Dan Multimedia Dengan Menerapkan Problem Based Learning (Pbl) Berbasis Learning Management System (Lms) - Khalimatus Sa’diyah; Harun Al Rosyid (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
The learning of User Interface (UI) elements in Text-Based, Graphic, and Multimedia Programming at SMKN Tambakboyo was still dominated by conventional, teacher-centered methods, resulting in suboptimal student engagement in problem-solving. This study aimed to (1) analyze the validity of a Problem Based Learning (PBL)-based Learning Management System (LMS) developed to support UI element learning, and (2) evaluate the difference in learning outcomes between classes taught using the PBL-based LMS and those taught with conventional classroom methods. This study employed a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The resulting product is a web-based LMS named EDUPRO, which integrates the PBL model with an AI-powered learning assistant feature called Edubot. The research subjects were 35 students of Class XI Software Engineering (RPL) at SMKN Tambakboyo, divided through ordinal pairing into an experimental group (18 students, PBL-based LMS) and a control group (17 students, conventional learning without a case-study approach on the EDUPRO LMS). Learning outcome data were analyzed using the Shapiro-Wilk test, Levene's Test, and the Independent Sample T-Test with the aid of RStudio. The results show that the EDUPRO LMS was categorized as Very Valid, with an overall average validation score of 93.29% (media validation 87.50%, material validation 96.36%, and test-item validation 96.00%). In terms of learning outcomes, the average posttest score of the experimental class (76.11) was significantly higher than that of the control class (64.41), with respective gain scores of 19.21 and 7.65. The Independent Sample T-Test produced t = 2.233 and Sig. (2-tailed) = 0.032 < 0.05, indicating that H₀ was rejected and H₁ accepted. Process, product, and reflection assessments of the experimental class also fell into the Very Good category, with average scores of 93.11%, 92.00%, and 85.00%, respectively. These findings confirm that the PBL-based EDUPRO LMS is both valid and effective in improving students' learning outcomes on the User Interface element.